Dysregulated bile acid metabolism as a novel player in gout progression: emerging therapeutic strategies - Sun, Hui; Yang, Le; Sun, Ye; Zhang, Xinya; Sun, Xin; Zhao, Xueping; Sun, Hui; Zhang, Qimeng; Yan, Guangli; Wang, Xijun (Frontiers in Endocrinology, 2025)
Gout, a prevalent metabolic disorder driven by hyperuricemia, results in pathological deposition of monosodium urate (MSU) crystals in joints and soft tissues, stimulating intense inflammatory responses with systemic health consequences. Emerging evidence highlights dysregulated bile acid (BA) metabolism as a pivotal contributor to gout pathogenesis. Imbalances in BA influence disease progression through multiple mechanisms (1): modulating hepatic urate production via PPAR-α/XOD signaling (2), regulating immune responses through FXR/TGR5-dependent suppression of NLRP3 inflammasome activation, and (3) shaping the gut microbiota composition, which reciprocally affects uric acid homeostasis and inflammation. Despite these advances, the precise mechanistic networks linking BA dysmetabolism to gout remain incompletely understood. In this review, we systematically synthesizes current knowledge on BA-gout interactions, elucidated how BA disturbances exacerbate disease progression, discussed the factors contributing to metabolic disorders of BAs, and evaluated promising therapeutic strategies targeting BA pathways. For example, FXR antagonists facilitate the synthesis of BA by inhibiting the aberrant activation of FXR. TGR5 agonists suppress inflammation. Probiotics help restore the diversity of the gut microbiota and increase the abundance of beneficial bacteria, including Bifidobacterium and Lactobacillus. Moreover, traditional Chinese medicine works by improving structural disorders of the gut microbiota and activating CYP7A1 to enhance the BA synthesis pathway. By integrating metabolic, immunological, and microbial perspectives, this work provides a framework for developing novel, mechanism-based interventions against gout.